Memorandum of understanding between Universiti Teknologi MARA and Gakushuin University / Akademi Pengajian Bahasa - Universiti Teknologi MARA, Akademi Pengajian Bahasa (Universiti Teknologi MARA (UiTM), 2020)
Memorandum of understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.